Badge Size Reflects Sperm Oxidative Status within Social Groups in the House Sparrow Passer domesticus - Rojas Mora, Alfonso; Meniri, Magali; Glauser, Gaëtan; Vallat, Armelle; Helfenstein, Fabrice (Frontiers in Ecology and Evolution, 2016)
The phenotype-linked fertility hypothesis proposes that male ornaments reflect male fertility. Male ornaments could honestly signal sperm quality due to the high susceptibility of sperm to free radicals on the one hand and the negative impact of oxidative stress on ornament elaboration on the other hand. Thus, only males with superior antioxidant defences could bear the cost of more elaborated sexual ornaments without suffering adverse fitness costs. Yet, in species where males experience differential access to fertile females, a trade-off emerges between investing into traits favouring mating opportunities (e.g. secondary sexual ornaments, social dominance, mate-guarding behaviours, etc.) or into traits favouring sperm competitive ability (e.g. sperm numbers and quality). When male sexual ornaments promote greater access to fertile females, a negative relationship can then be predicted between ornamentation and sperm quality. We tested the latter hypothesis and the phenotype-linked fertility hypothesis in wild House Sparrows Passer domesticus by exploring the relationships between sperm quality, melanin-based ornamentation, and redox status in blood and sperm. We found no correlation between badge size and sperm swimming performance. However, we found that within a social group, large-badged males better protect their ejaculates from oxidative stress, and thus produce less oxidized ejaculates. Additionally, we found that badge size did not reflect social dominance, and thus the protection of the ejaculate is independent of males’ ability to monopolize resources. Our results suggest that badge size might reflect male investment into the antioxidant protection of their sperm relative to a given social environment, and thus females may accrue both direct and indirect benefits by mating with large-badged males producing less oxidized ejaculates.